(untitled) (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: We know little about the level of physical activity, respiratory physiotherapy practices and nutritional status of people with primary ciliary dyskinesia (PCD), although these are important aspects of patients with chronic respiratory disease. We assessed physical activity, respiratory physiotherapy practices and nutritional status among people with primary ciliary dyskinesia in Switzerland, investigated how these vary by age and identified factors associated with regular physical activity. METHODS: We sent a postal questionnaire survey to people with primary ciliary dyskinesia enrolled in the Swiss PCD registry (CH-PCD), based on the standardised FOLLOW-PCD patient questionnaire. We collected information about physical activity, physiotherapy, respiratory symptoms and nutritional status. We calculated the metabolic equivalent (MET) to better reflect the intensity of the reported physical activities. To assess nutritional status, we extracted information from CH-PCD and calculated participants’ body mass index (BMI). RESULTS: Of the 86 questionnaires we sent, 74 (86% response rate) were returned from 24 children and 50 adults. The median age at survey completion was 23 years (IQR [interquartile range] 15–51), and 51% were female. Among all 74 participants, 48 (65%) performed sports regularly. Children were vigorously active (median MET 9.1; IQR 7.9–9.6) and adults were moderately active (median MET 5.5; IQR 4.3—6.9). Fifty-nine participants (80%) reported performing some type of respiratory physiotherapy. However, only 30% of adults saw a professional physiotherapist, compared with 75% of children. Half of the participants had normal BMI; one child (4%) and two adults (4%) were underweight. People who were regularly physically active reported seeing a physiotherapist more often. CONCLUSIONS: Our study is the first to provide patient-reported data about physical activity, respiratory physiotherapy and nutrition among people with primary ciliary dyskinesia. Our results highlight that professional respiratory physiotherapy, exercise recommendations and nutritional advice are often not implemented in the care of people with primary ciliary dyskinesia in Switzerland. Multidisciplinary care in specialised centres by teams including physiotherapists and nutrition consultants could improve the quality of life of people with primary ciliary dyskinesia.